Transcriptome analysis revealed the expression levels of genes related to abscisic acid and auxin biosynthesis in grapevine (Vitis vinifera L.) under root restriction - Wang, Lei; Li, Hui; Li, Jiajia; Li, Guanhan; Zahid, Muhammad Salman; Li, Dongmei; Ma, Chao; Xu, Wenping; Song, Shiren; Li, Xiangyi; Wang, Shiping (Frontiers in Plant Science, 2022)
The root system is essential for the stable growth of plants, which contributes to anchoring plants in the soil and plays a crucial role in water, mineral nutrient absorption as well as endogenous phytohormones formation. Root restriction cultivation (RR), a powerful technology, limits plant roots in a specific soil space. In the present study, roots of the one-year-old grapevine “Muscat Hamburg” under RR treatment and control (nR) treatment harvested at 70 and 125 days after planting were used for transcriptome sequencing, a total of 2031, 1445, 1532, and 2799 differentially expressed genes (DEGs) were obtained. The Gene Ontology (GO) enrichment analysis demonstrated that there were several genes in response to different phytohormone responses, including abscisic acid (ABA), auxin (IAA), ethylene (ETH), gibberellin (GA), and cytokinin (CTK). Among them, multiple genes such as PIN2 and ERF113 had involved in regulating the plant’s vital movements by various hormone pathways. Moreover, following the RR cultivation, DEGs are abundant in the biological processes of plant-type secondary cell wall biosynthesis, defense response, programmed cell death involved in cell development, and oxalate metabolic process. Furthermore, through joint analysis of transcriptome and previously published miRNA sequencing results, we found multiple differentially expressed miRNAs (DEMs) and DEGs combinations in different comparison groups showed an opposite defined trend, indicating that the expression levels of miRNA and its target genes were negatively correlated. Furthermore, RR treatment indeed significantly increased ABA content 125 days after planting and significantly decreased IAA content 70 days after planting. Under RR cultivation, most of ABA biosynthesis-related genes were up-regulated, while most of IAA biosynthesis-related genes were down-regulated. These findings laid a solid foundation for further establish the regulatory network of miRNAs regulating grapevine root development through target genes, as well as further explore molecular mechanism of endogenous ABA and IAA in regulating root architecture development in grape.